Improvement in policy and proactive interconnection procedure for renewable energy expansion in South Korea. (December 2018) - Kim, Sehyun; Lee, Hyunjae; Kim, Heejin; Jang, Dong-Hwan; Kim, Hyun-Jin; Hur, Jin; Cho, Yoon-Sung; Hur, Kyeon
Abstract: This paper presents the steps taken by the Korea Electric Power Corporation (KEPCO), the nation's only utility, to overcome limitations involved in increasing renewable energy penetration in an effort to support the government's movement for renewable energy expansion. While the government proposes reducing carbon dioxide emissions by 37% of the Business As Usual (BAU) value by 2030, which is about 315 million tonnes, it has improved energy policies for developing and deploying renewable energy technologies. To facilitate the integration of renewable energy into the future Korean power system, the government has announced a guaranteed interconnection policy for renewable energy sources under 1 MW. Based on this movement, the following measures have been enacted. First, examination of the hosting capacity of the current power system has been initiated to streamline the interconnection process for the distributed renewable energy sources and to reinforce the transmission and distribution network in a proactive manner. Second, to comply with reliability performance standards, an efficient planning procedure has been established for determining the optimal location and size of a renewable complex. To proceed with interconnection requests without delay, a prototype of a Renewable Energy Map (REM) based on PSS/e and Python has been developed. This tool facilitates more practical impact studies by incorporating capacity factors of renewable sources. In addition, it automates the screening process for determining suitable interconnection buses and feasible options for grid reinforcement. This tool is a step toward realizing the twin visions of "G-Platform" and "Carbon Zero" projects in Jeju Island." These efforts, which have been initiated in response to the Paris Climate Change Accord of 2015 and the 23rd Conference of the Parties 2017, aim to increase renewable energy from 7% to 20% of the total generated energy in Korea by 2030. Abstract : Highlights: The movement of the Korea government in improving support policy, interconnection procedure, and investments for renewable energy expansion. The movement of Korea Electric Power Corporation (KEPCO) in fully understanding current hosting capacity of the power system for enabling 'Guaranteed interconnection of renewable energy sources under 1 MW'. The movement of KEPCO and associated universities for developing renewable energy map (REM) for establishing foundation of predicting efficient installation of renewable energy aggregation without violating reliability standard. Current projects regarding renewable energy expansion.